Evaluation of Maturity Levels and Recommendations for Improvements to the Implementation of the Scrum Method : Case Study: SSM Transport and SSM QC Teams in Indonesia National Single Window Agency - Ihsan Lutfi; Achmad Nizar Hidayanto (AI Society & STMIK Indonesia, 2024)
This study examines the implementation of Scrum within LNSW’s national program, SINSW, focusing on two key projects, SSM QC and SSM Pengangkut. Despite adopting Scrum, deviations from its principles, such as unclear sprint end-dates, have hindered timely development. Using the Scrum Maturity Model (SMM), this research evaluates Scrum maturity through mixed methods, including KPA ratings and qualitative insights from observations, interviews, and document analysis. Results indicate both teams are at Maturity Level 1 (Initial), with SSM QC scoring 71.12% and SSM Pengangkut 64.7%, classified as Largely Achieved. Recommendations for advancing to Level 2 include defining clear sprint timelines, enhancing project management, quantitative metrics, team capabilities, and stakeholder involvement. Grounded in the Scrum Guide 2020 and SBOK V4, these strategies aim to refine Scrum practices, fostering more efficient project development at LNSW.